How adults with a profound intellectual disability engage others in interaction. Issue 4 (20th October 2016) - Antaki, Charles; Crompton, Rebecca J.; Walton, Chris; Finlay, W.M.L.
Abstract: Using video records of everyday life in a residential home, we report on what interactional practices are used by people with severe and profound intellectual disabilities to initiate encounters. There were very few initiations, and all presented difficulties to the interlocutor (support staff; the recording researcher); one (which we call 'blank recipiency') gave the interlocutor virtually no information at all on which to base a response. Only when the initiation was of a new phase in an interaction already under way (for example, the initiation of an alternative trajectory of a proposed physical move) was it likely to be successfully sustained. We show how interlocutors responded to initiations verbally, as if to neuro‐typical speakers – but inappropriately for people unable to comprehend, or to produce well‐fitted next turns. This mis‐reliance on ordinary speakers' conversational practices was one factor that contributed to residents abandoning the interaction in almost all cases. We discuss the dilemma confronting care workers.